Trend yields and the crop insurance program - Smith, Matthew K. (Kansas State University, 2012)
Multiple Peril Crop Insurance (MPCI) is a federally subsidized crop insurance program designed to mitigate risk for farmers across the United States. Many changes in technology and weather have increased yields in recent years. This has caused some to argue for the crop insurance program to consider yield trends when setting yields for the producer. This thesis evaluates alternative Actual Production History (APH) methods for corn to determine differences in the methods and the resulting APH. The key issue to be evaluated is that a producer’s APH may not be reflective of their “yield goal.” The thesis examined how the APH can differ under alternative methods of calculating an APH. Some methods examined are currently used by the Risk Management Agency (RMA). Other methods are hypothetical alternatives. This study examines alternative methods on a national, county, and a farm level. This thesis demonstrates that adjusting APHs for yield trends provides a higher APH than an un-trended APH. The 7 Year Olympic Trended APH provides the highest APH in most cases for all the methods examined. The RMA Un-trended APH proved to provide the least yield on average for all methods examined. This demonstrates the importance of adjusting for yield trends to factor in agricultural technology advancements over time.
Keywords: Crop insurance; Trend yields; Actual production history (APH); Corn; Risk management agency; Agriculture, General (0473); Business (0310); Economics, Finance (0508)